Fósseis do devoniano de goiás, Brasil (Sub-bacia alto garças, bacia do paraná) - Carbonaro, Fábio Augusto; Ghilardi, Renato Pirani [UNESP] (My University, 2016)
The fossil records of the Devonian of Goiás State (Alto Garças Sub-basin, Paraná Basin) occur in the cities of Amorinópolis, Iporá, Caiapônia, Rio Verde, and Doverlândia. However, the most fossils found in Goiás are brachiopods of the genus Derbyina, Australocoelia, Australospirifer, Schuchertella, Orbiculoidea, and Lingula. Although there are records of other groups as trilobites, molluscs, tentaculitids, annelids, echinoderms, lycopsids, and cnidarians. Chitinozoans are also found as Ramochitina, Ancyrochitina, Sphaerochitina, Angochitina, Conochitina, Lagenochitina, and Cyathochitina. However, the number of works about Devonian fossils of Goiás State is smaller when compared to the works published about the Devonian of Paraná State (Apucarana Sub-basin, Paraná Basin). This fact reflects to the low number of researchers working in this area. In sight of this, the objective of this study is to instigate the study of the Devonian fossils of Goiás, through the presentation of the fossils and its respective localities of occurrence in the Devonian of Goiás State, in addition to be pointed new outcrops which presented new records of fossils for this State.
Fossils of the Devonian of Goias, Brazil (Alto Garças sub-basin, Paraná Basin)